Study of surgical fixation of extra-articular distal third humerus fractures with a posterolateral locking compression plate - Kumar, Ravi; Karwasra, Ajay; Kunal, Kishore (International Journal of Research in Orthopaedics, 2019)
Background: Fractures of the adult distal humerus account for approximately 2% of all fractures and represent a third of all humerus fractures. Fractures of the distal third of the humerus are challenging injuries due to their peri-articular location, small size of the distal bone fragments, and the osteopenic quality of the bone in older adults. Aim of our study was to evaluate the clinical, radiographic and functional outcomes of posterolateral locking compression plate for extra-articular distal third humerus fractures through posterior triceps splitting approach. Methods: This is a prospective study done at All India Institute of Medical Sciences, Patna in which 30 consecutive skeletally mature, closed extra-articular distal humerus fractures underwent fixation with posterolateral locking compression plate and outcome evaluated in terms of radiological evidence of healing, functional outcome and complications if any. Results: Use of posterolateral plate results in predictably good union rates and excellent results terms of patient outcome without any implant related complications. Conclusions: We recommend using this posterolateral plate for these humerus fractures, because of its consistent results with respect to fracture union, stability across the fracture site and early mobilization for better functional results.